Television as an important component of the media: information and communication potential (Herald of Journalism, 2020)
The article discusses the place and role of television in shaping the culture of the information soci- ety, explores the features of television as an important component of the media. The authors pay special attention to the relationship between the state’s info-communicative level and the successful implemen- tation of the communicative and educational functions of television.The purpose of the scientific article is to analyze the important modern functions of television, to    study the processes of its transformation under the influence of modern technologies, and to forecast the preservation of information potential. The methodological basis of measuring the information impact of television on society is studied.The scientific and practical value of the study lies in determining the nature of the relationship be- tween the growing importance of television broadcasting and the needs of the audience. Humanity is getting used to living in an information society. As you know, in the documents of the World Summit, where the issues of the information society were discussed, new requirements for the means of mass communication were formulated. Including television, as the most popular media institute.The main results of the study. In the article, the authors analyze the communicative and enlighten- ing functions of television, identify the features of modern information and communication technologies that affect the formation of Kazakhstan’s information culture. The authors argue the importance of the cultural-forming function of television, while highlighting its educational features and gives the basic principles of its activities.The authors’ claims that the effective use of the educational functions of television and the benefits of new communication technologies require a high level of information culture of the society and the availability of modern information and communication infrastructure can be called a valuable conclusion to the work.In this paper, we study the problems of the functioning of Kazakhstani television in the context of the new legislation regulating the information policy of the state, taking into account the culture-forming, informational and educational properties of modern television. These recommendations can be used by domestic television channels to increase their potential in the new era and strengthen their influence in the system of relations between society and the state.
Keywords: information society, communication infrastructure, television, cultural and educational functions, information society culture, information policy, legal framework.